2009
DOI: 10.1177/0013161x09347341
|View full text |Cite
|
Sign up to set email alerts
|

Leadership for Literacy Coaching: The Principal’s Role in Launching a New Coaching Program

Abstract: Purpose: This study investigated the relationship between principal leadership and variation in teachers' participation in a new literacy coaching program: Content-Focused Coaching ® (CFC). Research design: Twenty-nine schools were randomly assigned to participate in the CFC program or to serve as a comparison. Interviews were conducted with elementary school principals and coaches, and teach ers completed surveys describing their experiences with their new coach. Correlation analyses investigated the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 42 publications
2
60
0
1
Order By: Relevance
“…Moreover, even in the CFC schools, coaching activities were an addition to teachers' regular duties and therefore competed for time with the teachers' other professional obligations. Unsurprisingly, lack of time has topped the list of reasons teachers identify for participating in coaching less frequently (Matsumura, Sartoris, Bickel, & Garnier, 2009). Other reasons have included teachers' belief that they would not benefit from coaching because their practice is fine as it is and their belief that the CFC program is just another program in a long list of reforms that eventually would pass on (Matsumura, Sartoris, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, even in the CFC schools, coaching activities were an addition to teachers' regular duties and therefore competed for time with the teachers' other professional obligations. Unsurprisingly, lack of time has topped the list of reasons teachers identify for participating in coaching less frequently (Matsumura, Sartoris, Bickel, & Garnier, 2009). Other reasons have included teachers' belief that they would not benefit from coaching because their practice is fine as it is and their belief that the CFC program is just another program in a long list of reforms that eventually would pass on (Matsumura, Sartoris, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In many of the CFC schools, the newly recruited Cohort 2 teachers experienced a different professional culture in their first year than did the Cohort 1 teachers. Interviews with coaches indicated that most of them established a more regular pattern of meeting with teachers in collaborative settings in the second year of the trial, compared to the first trial year in which most of their efforts focused on building relationships with principals and teachers (Matsumura, Sartoris, et al, 2009). Further analyses rendered evidence that the norms for professional collaboration changed in the CFC schools after the first year of the program.…”
Section: Teachers' Experiences Of Coachingmentioning
confidence: 97%
“…In some schools, coaches' primary work focuses on collaborating with teachers to improve their practice. However, in many schools, coaches are responsible for administrative tasks, assessment coordination, and direct work with students (Bean et al, 2010;Matsumura, Sartoris, Bickel, & Garnier, 2009). These additional responsibilities can interfere with the time coaches have to work with teachers (Coburn & Russell, 2008;Firestone & Martinez, 2007;Mangin, 2008).…”
Section: Report On the Implementation Of No Child Leftmentioning
confidence: 99%
“…These additional responsibilities can interfere with the time coaches have to work with teachers (Coburn & Russell, 2008;Firestone & Martinez, 2007;Mangin, 2008). The way teachers engage with coaching is also influenced by principals' approach to working with coaches (Matsumura et al, 2009) and principals' willingness to share leadership responsibilities with the staff (Matsumura, Garnier, & Resnick, 2010).…”
Section: Report On the Implementation Of No Child Leftmentioning
confidence: 99%
See 1 more Smart Citation